2014
DOI: 10.4103/0301-4738.133522
|View full text |Cite
|
Sign up to set email alerts
|

ALK negative inflammatory myofibroblastic tumor of the orbit:A masquerading entity

Abstract: Inflammatory myofibroblastic tumor is a biologically distinct neoplasm of intermediate grade, which can affect every possible tissue of the human body. It is a ‘masquerading tumor’ as the presenting complaints vary with the affected site. Occurrence of this tumor as an orbital mass is rare and is challenging for both the clinician as well as the pathologist, due to a varied number of lesions sharing a similar picture clinically and histologically. We discuss a rare case of inflammatory myofibroblastic tumor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Grossly, the tumor is well-circumscribed, lobulated or multinodular and may be firm or fleshy with a tan-white cut surface [ 3 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grossly, the tumor is well-circumscribed, lobulated or multinodular and may be firm or fleshy with a tan-white cut surface [ 3 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steroid refractory IMT requiring alternate agents is well documented [ 13 ]. Paradoxically emergence of IMT whilst on immunosuppression following kidney transplant has been reported putting into perspective the basis of immunosuppressive treatment in the management of IMT [ 11 ]. The definitive role of glucocorticoid therapy in IMT is not clearly understood but a therapeutic trial should be considered in appropriate cases and continued into remission if clinical and radiological response is apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies revealed persistently elevated inflammatory markers with the lowest documented C - reactive protein level of 96 mg/dL and erythrocyte sedimentation rate of 132 mm in the first hour. Whole blood analysis demonstrated normal red cell indices (haemoglobin of 11.2 g/dL) with mildly elevated white cell count of 13.48 × 10 9 /L [ 4 - 11 ] which was predominantly neutrophilic - 67.8%. Blood film did not yield any additional information.…”
Section: Case Presentationmentioning
confidence: 99%
“…Our patient presented with a mass arising from perilimbal area. The other reported cases presented with a subconjunctival mass inducing diplopia [ 1 ], a mass inferior to inferior rectus muscle with multiple neuropathy [ 5 ], painful exophthalmos [ 6 ], painless gradual diminution of vision for 2 months [ 9 ], supraorbital mass with loss of vision and phthisis for 2 years [ 10 ], and rapid progressive painless proptosis [ 8 ]. The case that was most similar to ours was an eight-month-old infant, who presented with a 5-week history of painless progressive swelling in the left upper eyelid [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple cranial nerve involvement (II, V1, V2, V3, and X) was only seen in the case of a fifty-year-old adult patient [ 5 ], while the CT of another case showed an intraconal mass of left orbit that was not well differentiated by the lacrimal gland [ 6 ]. The MRI orbit of one case showed a smooth lobulated mass involving the superior and lateral aspects of the right orbit with involvement of the greater wing of sphenoid bone [ 9 ]. Bone erosion was not seen in any of these cases.…”
Section: Discussionmentioning
confidence: 99%